Topology Optimization of Wind Power Photovoltaic Energy System Based on Quantum Optimization Algorithm - Ding, Weibin; Zhang, Deqi; Yang, Junjia; Chen, Yanzuo (2024 4th International Conference on Energy Engineering and Power Systems (EEPS), 2024)
Because the traditional method does not consider the quantum optimization factor, the topology effect of wind power photovoltaic energy system is not good, so the topology optimization of wind power photovoltaic energy system based on quantum optimization algorithm is proposed. Calculating quantum mapping sequence, setting initial parameters, initializing quantum position, establishing topology optimization objective function, setting constraint conditions for topology optimization balance of wind power photovoltaic energy system, calculating charging and discharging power of wind power photovoltaic energy system, adjusting state of wind power photovoltaic energy system, and designing topology optimization flow of wind power photovoltaic energy system. The experimental results show that this method has obvious advantages in reducing the peak-valley difference of wind power photovoltaic energy system load, the energy storage capacity is close to the expected configuration, and the topology optimization effect is better.